On the impact of safety requirements, energy prices and investment costs in street lighting refurbishment design. (15th December 2018) - Beccali, M.; Bonomolo, M.; Leccese, F.; Lista, D.; Salvadori, G.
Abstract: Street lighting is an indispensable feature for the night landscape of cities. It is important for road safety, users visual comfort, crime prevention and to augment the perceived personal safety. Realize and maintain an adequate street lighting service is very expensive for municipalities with significant impact on their budgets. For this reason, special attention should be paid to the design of new street lighting systems and to the refurbishment of existing ones, since many of them are inadequate. In light of this it is very important to implement street lighting designs that fulfil lighting requirements avoiding energy waste and light pollution and, at the same time, result economically sustainable for municipalities. In this paper, an original step by step methodology for the lighting, energy and economic analysis of street lighting refurbishment designs has been introduced and explained in detail. The methodology is suitable for use in cities of different sizes. As an applicative example, the methodology has been tested in the town of Pontedera (Italy) and the results are discussed, also providing a sensitivity analysis of the economic feasibility with respect to the variations of electricity prices and investment costs. Highlights: Typical critical issues of public street lighting in Italian towns are analysed. A methodology for street lighting systems refurbishment in small/medium sized Italian towns is proposed. A multi-objectives analysis (lighting, energy and economic parameters) is adopted for lighting design evaluation. The case study of Pontedera town (Italy) street lighting refurbishment is discussed. Benefits from the use of the adopted methodology are exposed.